Efficient multi-user efficiency realization mechanism by user co-operative motion - et. al., K.Pazhanisamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multi-user co-operative motion is a novel method to progress the efficiency in mobile adhoc networks system (MANETs). Related with old-style techniques such as bandwidth expansion and increasing the effectiveness of broadcast protocol, this method decreases the communication cost of setup, storage overhead, and energy intake through the motion of users. Our developed multi-user co-operative motion in current usage becomes an important issue. Most of the developed method use a single motion user and do not implement the multi-user co-operative motion setups. We have developed a new scheme named, Efficient Multi-user Efficiency realization method (EME) based on the known topographical location data of static users. Simulation analysis display that the efficiency of EME is increased when compared to other methods. Communication time of our developed method is less when compared to the other methods. Our developed method is effective in improving the effectiveness, reducing communication overhead in multi-user co-operative motion methods.